2021
DOI: 10.1093/braincomms/fcab021
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic differences in the hippocampus and cortex of epilepsy brain tissue

Abstract: Epilepsy is a common neurological disorder affecting over 70 million people worldwide, with a high rate of pharmaco-resistance, diverse comorbidities including progressive cognitive and behavioral disorders, and increased mortality from direct (e.g., sudden unexpected death in epilepsy, accidents, drowning) or indirect effects of seizures and therapies. Extensive research with animal models and human studies provides limited insights into the mechanisms underlying seizures and epileptogenesis, and these have n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 108 publications
5
61
2
Order By: Relevance
“… 35 , 36 Whole exome sequencing in surgical brain tissue from epilepsy patients that died from SUDEP implicate several gene variants that may increase risk of SUDEP. 58 , 59 We recently identified a number of protein differences between epilepsy and non-epilepsy control cases by localized proteomics in cortex and hippocampal CA1-3 and DG, 60 however found no significant protein differences when comparing SUDEP to epilepsy and few differences in the hippocampus of high-risk SUDEP MTLE cases with a prolonged PGES by RNAseq. 39 Future studies should validate molecular markers to better understand SUDEP risk and to potentially identify novel markers in brain tissue.…”
Section: Discussionmentioning
confidence: 98%
“… 35 , 36 Whole exome sequencing in surgical brain tissue from epilepsy patients that died from SUDEP implicate several gene variants that may increase risk of SUDEP. 58 , 59 We recently identified a number of protein differences between epilepsy and non-epilepsy control cases by localized proteomics in cortex and hippocampal CA1-3 and DG, 60 however found no significant protein differences when comparing SUDEP to epilepsy and few differences in the hippocampus of high-risk SUDEP MTLE cases with a prolonged PGES by RNAseq. 39 Future studies should validate molecular markers to better understand SUDEP risk and to potentially identify novel markers in brain tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Case history for the 19 control and 19 SUDC cases is summarized in Table 1 , detailed further in Tables 2 , 3 and Supplementary Table 1, online resource. Group sizes were determined based on the number of cases with significant findings as previously reported [ 33 , 50 , 65 ], including our previous study in epilepsy cases with similar methods [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Label-free quantitative MS was performed to identify differential protein expression, as described previously [ 43 , 60 ]. Proteins were extracted and digested in each brain region separately in random batches of 16 samples according to S-Trap protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Recent Advances in Neurochemistry the majority of instances, seizures can be controlled, however approximately 30% of cases are treatment resistant. Seizures arise from abnormal synchronous activity in hyperexcitable neuronal networks and while this can be attributed to altered electrophysiological properties of ion channels and neurotransmitter systems, converging lines of research have also indicated a central role for the regulation of protein translation [122,123].…”
Section: Epilepsymentioning
confidence: 99%